PENGARUH RISIKO PADA E-COMMERCE - Soegoto, Eddy Soeryanto; Putera, Muhammad Habibi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study examines the effect of consumer confidence and risk on e-commerce buying interest. The research method used a multiple linear regression test with the help of the SPSS program. This type of research was qualitative by interviewing random sampling students of Universitas Komputer Indonesia who are majoring in information systems. The variables of this study were the consumer's confidence (X1) and risk (X2), which are independent, as well as the purchase interest variable (Y) as the dependent variable. The results showed that risk and consumer confidence significantly influenced buying interest in E-Commerce. An e-commerce website needs to provide helpful information and the right strategy in building a consumer's trust. The company can also display innovations on its website so that buyers can easily understand the flow of payments and guarantee personal data security. Besides, companies also need to provide security and assurance to consumers while making transactions in e-commerce.